Enhancing Pedagogical Development of Natural Science Teachers Through a Key Concepts in Science Project: A Social Constructivist Perspective - Botes, Wiets; Philip, Anita (Research in Social Sciences and Technology- OpenED Network, 2025)
This study investigated whether the Key Concepts in Science Project influenced the pedagogical development of Natural Science teachers. Grounded in social constructivism, emphasising collaborative learning and hands-on interaction, the study employed qualitative methods to collect empirical data. Through photographic evidence, field notes, and focus group discussions with participating teachers, the study unveiled several themes, including the mastery of practical teaching approaches, horizontal and vertical knowledge articulation in syllabus delivery, sharing of best practices, and the significance of practical demonstrations in school settings. Field notes highlight rich information sharing and teacher commitment to professional development. The findings underscore the pivotal role of partnering with local community schools in fostering teacher optimism, resilience, and ongoing professional growth. This research offers valuable insights for educators seeking to enhance practical teaching skills and promote effective science education.